Second Impressions: Expanding the Range of Cereals from Early Neolithic Franchthi Cave, Greece - Allen, Susan E. (Ethnobiology Letters, 2018)
The southern Greek archaeological site of Franchthi Cave, with occupation dating from the Upper Paleolithic, remains the only site in southern Greece that both spans the shift from foraging to farming and has produced systematically recovered plant remains associated with this important transition in human prehistory. Previously reported archaeobotanical remains from the site derive exclusively from the cave interior, as none were recovered from outside the cave on the Franchthi Cave Paralia. This article reports the first evidence for plant use in the settlement area outside the cave, as provided by five seed impressions in Early Neolithic ceramic sherds from the Paralia. Significantly, this new data expands the range of crops represented at the site during the Early Neolithic to include einkorn wheat (Triticum monococcum L.), pushing back its appearance at Franchthi by several centuries.